2007
DOI: 10.1055/s-2006-950357
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylenetetramine-Mediated Transesterification of β-Keto Esters

Abstract: H e x a m e t h y l e n e t e t r a m i n e -M e d i a t e d T r a n s e s t e r i f i c a t i o n o f b -K e t o E s t e r s Abstract: Treatment of methyl or ethyl b-keto esters with primary, secondary, or tertiary alcohols in the presence of a catalytic amount of hexamethylenetetramine results in good to high yields of the corresponding esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the course of our research on the application of βdicarbonyl compounds for the synthesis of heterocycles and carbocycles using multicomponent reactions [3,[11][12][13][14][15][16][17] , I needed to prepare chiral β-keto esters and found that currently existing methods were not wholly satisfactory. We report now the development of a modified synthetic procedure for the practical synthesis of acetoacetates 3 from 2, 2, 6-trimethyl-4H-1, 3-dioxin-4-one (1) and alcohols, including chiral alcohols, or primary or secondary amines under mild conditions that avoid side reactions and give essentially quantitative yields.…”
Section: ~ 190 ~mentioning
confidence: 99%
“…In the course of our research on the application of βdicarbonyl compounds for the synthesis of heterocycles and carbocycles using multicomponent reactions [3,[11][12][13][14][15][16][17] , I needed to prepare chiral β-keto esters and found that currently existing methods were not wholly satisfactory. We report now the development of a modified synthetic procedure for the practical synthesis of acetoacetates 3 from 2, 2, 6-trimethyl-4H-1, 3-dioxin-4-one (1) and alcohols, including chiral alcohols, or primary or secondary amines under mild conditions that avoid side reactions and give essentially quantitative yields.…”
Section: ~ 190 ~mentioning
confidence: 99%